Perceived drivers of the Ebola virus disease outbreak in Mubende and Kassanda districts, Uganda: a qualitative study - Ninsiima, L.R.; Mor, Siobhan M.; Romano, J.S.; Namakula, L.N.; Kankya, C.; Kungu, J.; Mugisha, L.; Klein, J.; Nyakarahuka, L. (BMJ, 2024)
Introduction: During the most recent Ebola virus disease (EVD) outbreak in Uganda, a cluster of community deaths with epidemiological linkages to the first reported case were identified to have occurred in Mubende, Kassanda and Kampala districts in September 2022. This study aimed to explore perceived drivers of EVD outbreak among affected communities in Mubende and Kassanda districts, Uganda.